Campus visits & college interviews : a complete guide for college-bound students and their families - Schneider, Zola Dincin; Schneider, Zola Dincin (New York : College Board : Distributed by H. Holt and Co., 2002)
How to get the most out of your campus visits, and get the stress out of your college interviews. Updated to give the pros and cons of college Web sites and "virtual visits, " and reformatted with easy-to-use charts and checklists, this quick and handy guide will help you get the right impression during your visit and make the right impression during your interview. It tells you the best times to visit; what to look for while you're there; what questions to expect during your interview; what questions you should ask; and more.
Rev. ed. of: Campus visits and college interviews. 1997 or 1998.
Keywords: College choice -- United States; Campus visits -- United States; College student orientation -- United States; Interviewing; colegio elección -- Estados unidos; visitas a los campos -- Estados unidos; Orientacion a los estudiantes universitarios -- Estados unidos; Entrevistas